Voltammetric analysis of dantrolene and its active metabolite with indomethacin in rat plasma. (12th December 2018) - Ragab, Marwa AA; Korany, Mohamed A; Galal, Shereen M; Ahmed, Aya R
Aim: Differential pulse polarography was used for the concurrent analysis of the coadministered dantrolene (DAN) and indomethacin (IND) in plasma.Materials & methods: DAN and IND, Hanging mercury drop electrode and Britton–Robinson buffer at pH 5 were used. In plasma, cathodic reduction of DAN nitro group and its active metabolite at -0.2 V was done. IND was analyzed after carbonyl group reduction at -1.1 V.Results: Drugs determination in rat plasma with good recoveries and low limit of quantitation was done. Application to trace analysis of drugs in rat plasma was done with Cmax and Tmax determination.Conclusion: This technique shows high sensitivity, simplicity and low cost. The method is US FDA validated and it is applicable to human level.